Is the COVID‐19 Pandemic a High‐Risk Period for College Student Alcohol Use? A Comparison of Three Spring Semesters. (23rd March 2021) - Jaffe, Anna E.; Kumar, Shaina A.; Ramirez, Jason J.; DiLillo, David
Abstract : Background: There has been widespread concern that the COVID‐19 pandemic may be a high‐risk time for alcohol use among heavy drinking populations such as college students. Initial efforts to evaluate changes in college drinking have not yet accounted for typical drinking patterns within a semester. Methods: To fill this gap, we evaluated how college student drinking patterns changed with the onset of restrictions related to the COVID‐19 pandemic during spring 2020 relative to spring 2018 and 2019. Participants were 1, 365 college students aged 19 and older, including 895 students who reported past‐month alcohol use. Daily drinking data were extracted from an online Timeline Followback survey. Results: Negative binomial hurdle models revealed that, with the onset of the COVID‐19 pandemic in spring 2020, college student drinkers did not increase their drinking frequency as was typical in late spring semester, and the number of drinks per occasion declined substantially (28% reduction), greater than the change observed from early to late spring 2018 (3% reduction) or spring 2019 (8% increase). This reduction in drinking quantity in spring 2020 was larger for college student drinkers who moved residences because of the pandemic (49% reduction) than students who did not move (21% reduction). Perceptions in pandemic‐related changes in drinking also revealed that 83.5% of college student drinkers self‐reported that their drinking stayed the same or decreased. Conclusions: Findings suggest that, on average, college students drank less—not more—during the onset of the COVID‐19 pandemic and highlight the importance of living situation in college student drinking behavior. More research is needed to assess alcohol use in other universities, as this information could be utilized in norms‐based interventions to further reduce drinking in students who remain at risk. Abstract : To evaluate changes in college student drinking during the onset of the COVID‐19 pandemic, we examined alcohol use patterns among three cohorts of US college students ( N = 1, 365). Although drinking frequency increased from early to late spring in 2018 and 2019, no such increase was observed in 2020. Whereas drinking quantity remained relatively stable from early to late spring in both 2018 and 2019, the number of drinks consumed per occasion decreased by 28% in 2020.